Continued training and knowledge for teaching in integrated middle school (Research, Society and Development, 2019)
The present article sought to understand the contributions of teacher training and knowledge in secondary education integrated with technical vocational education. For that, a bibliographic research was carried out for a clearer view of the investigated object. In the light of the authors used in the theoretical framework, it is concluded that the school context is a fertile environment for the continuing education of high school teachers integrated with technical vocational education, for it, the teacher must be protagonist and be contemplated knowledge capable of developing the scientific-reflective competence, seeking an integrative pedagogical practice.